Hello
<span>an equation for the line in point-slope form and general form is :
y = ax+b a : </span>slope ; the <span>Passing through (x' ; y')
</span>y' = ax'+b
y-y' =a(x-x') and : x' =2 y' = - 1
calculate a :
let : y = ax+b .....(D)
....<span>3y-x=7</span>....(D') or y = (1/3)x+7/3
.(D) perpendicular to(D') : slope (D) × slope (D') = -1
slope (D') = 1/3
slop(D)×(1/3) = -1
slope (D) = -3
equation for the line : y-y' =a(x-x')
y+1 =(-3) (x-2)
1. archaic
2. evangelists
3. Norman’s
4. John Wycliffe
5. Vulgar
Answer:
0.6
Step-by-step explanation:
2×3x+4+4=12
6X+8=12
6x=12-8
6x=4
Divide by 6
X=0.6
Answer:
False
False
True
False
True
Step-by-step explanation:
I hope this helps!
<span>6(-3m)^4
= 6(-3)^4 m^4
= 6(81) m^4
= 486 m^4
on your options answer is </span><span>C.6(-3)^4m^4</span>